2019
DOI: 10.1016/j.ibusrev.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

How anticipated regret influences the effect of economic animosity on consumers’ reactions towards a foreign product

Abstract: We use regret theory to explain the negative effect of economic animosity on consumers' reactions towards a foreign product (i.e., product judgment and reluctant to buy). We conduct our study in Taiwan by collecting data via an online survey. Our results show that consumers' economic animosity increases their anticipated regret towards purchasing a foreign product originating from a target market of animosity. Specifically, anticipated regret is found to mediate the link between economic animosity and foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
5
28
0
1
Order By: Relevance
“…This means that the higher ethnocentric consumers will increase the animosity toward foreign products. The results of this study are in line with previous studies conducted by those who revealed that consumer ethnocentrism influences animosity (Quang et al, 2017;Souiden et al, 2018;Khan et al, 2019).…”
Section: The Relationship Between Consumer Ethnocentrism Animosity Tsupporting
confidence: 92%
See 1 more Smart Citation
“…This means that the higher ethnocentric consumers will increase the animosity toward foreign products. The results of this study are in line with previous studies conducted by those who revealed that consumer ethnocentrism influences animosity (Quang et al, 2017;Souiden et al, 2018;Khan et al, 2019).…”
Section: The Relationship Between Consumer Ethnocentrism Animosity Tsupporting
confidence: 92%
“…This means that animosity toward foreign products cannot influence imported product judgment. The results of this study are in line with previous research which suggests that animosity toward foreign products is not able to predict imported judgment products (Ahmed et al, 2013;Kiriri, 2019;Quang et al, 2017;Khan et al, 2019).…”
Section: The Relationship Between Consumer Ethnocentrism Animosity Tsupporting
confidence: 89%
“…In consumption contexts, increasing the salience of regret anticipation has been found to make consumers (1) turn to conventional options (Shefrin and Statman 1985); (2) prefer high-priced, well-known brands over cheaper but less-known products (Simonson 1992); (3) opt for status quo alternatives (Lemon, White, and Winer 2002); and (4) make investment decisions that shield them from the possibility of experiencing regret even when these are associated with heightened risk or uncertainty (Zeelenberg and Pieters 2007). In addition, regret anticipation has been shown to explain consumers’ aversion to brands originating from countries toward which consumers hold feelings of economic animosity (Khan, Daryanto, and Liu 2019) as well as their willingness to accept products incorporating major technological innovations (Jiang, Chakravarthi, and Turut 2016). Recent research has also shown that although anticipated regret is generally associated with higher levels of choice deferral, when consumers feel situationally empowered, anticipated regret subsides, thus making the consumer more likely to commit to a choice than defer it altogether (Mourali et al 2018).…”
Section: Conceptual Background and Research Hypothesesmentioning
confidence: 99%
“…Finally, most relevant research has focused on cognitive constructs and has neglected emotions as antecedents or consequences of global/local brand choices. Despite calls for research in this area (Gürhan-Canli, Sarıal-Abi, and Hayran 2018), with the exception of a couple of studies (Davvetas and Diamantopoulos 2018; Khan, Daryanto, and Liu 2019), to the best of our knowledge, no research has explicitly investigated the effect of emotional primes on global/local brand preference in consideration sets including both brand types.…”
mentioning
confidence: 99%
“…Os aspetos cognitivos do arrependimento, diferentemente de outras emoções negativas como o medo ou a raiva, é uma emoção cognitivamente mais elaborada (Khan et al, 2019). Inman, Dyer e Jia (1997) afirmam que o consumidor experimentará o arrependimento sempre que o desempenho do produto escolhido for inferior ao desempenho de um produto preterido no processo de tomada de decisão.…”
Section: Arrependimentounclassified